Reduced cell size, chromosomal aberration and altered proliferation rates are characteristics and confounding factors in the STHdh cell model of Huntington disease. Issue 1 (December 2017) - Singer, Elisabeth; Walter, Carolin; Weber, Jonasz; Krahl, Ann-Christin; Mau-Holzmann, Ulrike; Rischert, Nadine; Riess, Olaf; Clemensson, Laura; Nguyen, Huu
Abstract Huntington disease is a fatal neurodegenerative disorder caused by a CAG repeat expansion in the gene encoding the huntingtin protein. Expression of the mutant protein disrupts various intracellular pathways and impairs overall cell function. In particular striatal neurons seem to be most vulnerable to mutant huntingtin-related changes. A well-known and commonly used model to study molecular aspects of Huntington disease are the striatum-derived STHdh cell lines generated from wild type andhuntingtin knock-in mouse embryos. However, obvious morphological differences between wild type and mutant cell lines exist, which have rarely been described and might not have always been considered when designing experiments or interpreting results. Here, we demonstrate that STHdh cell lines display differences in cell size, proliferation rate and chromosomal content. While the chromosomal divergence is considered to be a result of the cells' tumour characteristics, differences in size and proliferation, however, were confirmed in a second non-immortalized Huntington disease cell model. Importantly, our results further suggest that the reported phenotypes can confound other study outcomes and lead to false conclusions. Thus, careful experimental design and data analysis are advised when using these cell models.